Satisfaction Relationship Of Outpatient Clinic Towards The Pharmacy Installation's Services With Interest To Re-Purchace Prescription Drugs In Pharmacy Installation Of General Hospital Dr. Soedirman Kebumen - Sodik, Anwar; Handayani, Eka Wuri; Darmawan, Endang; Pramono, Muji (Sean Institute, 2022)
Competition in the hospital business makes patient satisfaction the priority. Customer satisfaction. Therefore, the hospital needs to assess what factors will affect patient satisfaction and whether patient satisfaction is met to maintain the patient. This study is descriptive and analytical with a quantitative approach, this study design was a cross-sectional survey. Data was collected through questionnaires to 370 respondents in the pharmacy installation of General Hospital dr. Soedirman Kebumen. Data analysis was performed by bivariate analysis using chi-square with SPSS 15.0 programs. Based on the five dimensions of service satisfaction, the smaller the P value, the more influential it is in increasing or decreasing the interest in re-purchase drug prescriptions at Dr. Soedirman Hospital, Kebumen. From this study, the smallest P value is the tangible dimension, namely 0.001, followed by the reliability dimension of 0.009. This shows that the most important role in increasing interest in re-purchase prescription drugs are the facilities and infrastructure, as well as the waiting time for pharmaceutical services